pharmaceutical-sciences 2018
DOI: 10.4172/pharmaceutical-sciences.1000339
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging and Antibacterial Activity of Phenolic Compounds from Anacardium occidentale L. Stem Barks from South East Sulawesi-Indonesia

Abstract: Wahyuni, et al.: Radical Scavenging and Antibacterial Potencies of Anacardium occidentale Stem Barks Three phenolic compounds, pinostrobin, pinocembrin and 4-hydroxybenzaldehide have been isolated and identified for the first time from methanol extract of Anacardium occidentale L. stem bark. The isolation was carried out using various techniques of chromatography such as thin layer chromatography, vacuum liquid chromatography and radial chromatography. Silica gel as adsorbent and a mixture of solvents as eluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The results revealed that methanolic extract exhibited strong antioxidant activity in the DPPH assay with an IC50 value of 87.67 μg/mL. This finding is similar to previous study which showed high antioxidant capacity of stem barks and leaves extracts of A. occidentale (Olatunji, 2015;Uni et al, 2018).…”
Section: Antioxidant Activitysupporting
confidence: 89%
See 1 more Smart Citation
“…The results revealed that methanolic extract exhibited strong antioxidant activity in the DPPH assay with an IC50 value of 87.67 μg/mL. This finding is similar to previous study which showed high antioxidant capacity of stem barks and leaves extracts of A. occidentale (Olatunji, 2015;Uni et al, 2018).…”
Section: Antioxidant Activitysupporting
confidence: 89%
“…Phytochemical studies on this species revealed the presence of various secondary metabolites, which are of potential medicinal uses. Studies have found that some of these compounds extracted from A. occidentale exhibit biological activities such as antioxidant, anti-inflammatory, antibacterial, antimicrobial, antitumor, anti-mutagenic, and anti-allergic (Olatunji, 2015;Uni et al, 2018;Yuliana et al, 2014;Aracelli et al, 2016). The main focus was on the extraction, isolation, and characterization of compounds from the stem barks of A. occidentale.…”
Section: Introductionmentioning
confidence: 99%
“…Chloramphenicol exhibited inhibition zones of 18.71 to 21.50 mm. The IC 50 varied from 62.5 to 500 (4,098 µM), with the best effect being obtained using the extract against all strains (46).…”
Section: In Vitro Studies Antibacterial Propertiesmentioning
confidence: 99%